2020
DOI: 10.3897/ap.2.e2609
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties and Resources of Teachers’ Adaptation in Teachers’ Reflection

Abstract: Improving the quality of teacher's training can be difficult without analyzing the crucial problems and resources to overcome the former which exist at the initial stage of the teacher's work. The article is devoted to this relevant problem. The aim of the article is a comprehensive analysis of factors that are actualizing the capacity of school teachers at the initial stage of their work. The leading method for researching the problem is the authors' questionnaire "Reflection on early pedagogical experience".… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…AL-Naimi et al ( 2020) found that novice teachers may lack planning skills and they should have extensive professional development sessions and work on evaluating, developing, and revising lesson plans. The findings of a study done by Warren and Warren & Miller (2013) in Australia indicated that very few novice teachers posted to rural areas are prepared to teach effectively and that novice teachers need to have a good references to deepen their knowledge and acquire general professional competencies, self-knowledge, and self-development While Usoltseva et al (2020) found that it is important these teachers of modern pedagogical technologies for the beginning teacher. So work states that we should be motivating these teachers t…”
Section: Professional Challengesmentioning
confidence: 99%
“…AL-Naimi et al ( 2020) found that novice teachers may lack planning skills and they should have extensive professional development sessions and work on evaluating, developing, and revising lesson plans. The findings of a study done by Warren and Warren & Miller (2013) in Australia indicated that very few novice teachers posted to rural areas are prepared to teach effectively and that novice teachers need to have a good references to deepen their knowledge and acquire general professional competencies, self-knowledge, and self-development While Usoltseva et al (2020) found that it is important these teachers of modern pedagogical technologies for the beginning teacher. So work states that we should be motivating these teachers t…”
Section: Professional Challengesmentioning
confidence: 99%